The effectiveness of using augmented reality in teaching geography curriculum on the achievement and attitudes of Omani 10th Grade Students - Khalfan Al Shuaili; Ali Sharaf Al Musawi; Raja Muznah Hussain (Multidisciplinary Journal for Education, Social and Technological Sciences)
This study aimed to investigate the effectiveness of using a mobile Augmented Reality application in the geography unit for 10th-grade students on their achievements and attitude. The unit is part of the Omani’s social studies curriculum and entitled, “Environmental Problems and Hazards”. To achieve this purpose, a quasi-experimental study design was conducted. The instruments designed, validated and used to collect data were pre-post achievement tests and attitudinal scale. The participants were 64 male students, divided into two experimental and control groups. The field application period took four weeks in which the control group studied the unit using the normal teaching method, while the mobile Augmented Reality application, HP Reveal, with a website that supports its features, was integrated to teach experimental group. Findings show that there was a statistically significant difference between the pre- and post-field applications in terms of students’ achievement and attitudes. Nevertheless, there was no impact observed when the control and experimental groups’ achievement was compared.  The researcher suggested conducting further investigations to examine the value of integrating Augmented Reality in the educational system considering various factors and variables.